Advancements in Chemical Materials: Exploring Smart Storage Equipment and Protection Systems (Review) - Samah Kamil; Mohammed Al-Turfi; Riyadh Almukhtar (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
The growing dependence on chemicals across industries has emphasized the importance of storage solutions to ensure safety and environmental sustainability. Smart storage systems, equipped with cutting-edge technologies, offer opportunities to tackle these issues guaranteeing best dealing and handling. This study evaluates chemical storage equipment and protection systems' role in increasing safety and sustainability in storage practices and roles. This evaluation included a decade-long literature examination of papers, patents, and industry reports. The analysis examined safety assessments, regulatory compliance, and storage system applications. The study examined IoT, AI, sophisticated detectors, and sensors to improve storage safety and reduce the effect for environmental sustainability. Results showed breakthroughs in sensor technologies, systems integration, and AI algorithms for real-time storage facility monitoring, danger identification, and predictive analytics. Smart storage solutions reduce hazards, ensure compliance, and protect the environment. However, prices, integration issues, and data security concerns were noted. Overall, this review sheds light on chemical smart storage systems and their future. It shows how technology improves safety and sustainability and identifies topics for further research.